Penyalahgunaan Narkotika ditinjau dari Viktimologi berdasarkan undang-undang nomor 35 tahun 2009 tentang Narkotika di Daerah Istimewa Yogyakarta - Arinatha Fardian; Sigit Herman Binaji; Suryawan Rahardja (Universitas Janabadra, 2019)
Legal protection efforts for narcotics abuse victims are based on Law Number 35 of 2009 concerning Narcotics which can be in the form of sanctions for action. This study aims to determine victims of narcotics abusers in terms of victimization based on Law Number 35 Year 2009 and legal protection for victims of narcotics abusers and the obstacles they face. Data collected from the results of research, both library research and field research, are then analyzed descriptively qualitatively, namely the method of data analysis by grouping data and selecting data obtained from research according to its quality and truth, then linked to laws and theories obtained from the literature, so obtained answers to the problems studied. Victims of narcotics abusers in terms of victimization based on Law Number 35 Year 2009 are those who unintentionally use narcotics, because they are persuaded, tricked, tricked, forced, and / or threatened to use narcotics. However, in practice those who are considered victims are those who have just been first caught red-handed with evidence that does not exceed those stipulated in the Supreme Court Circular Letter Number 4 of 2010. Legal protection for victims of narcotics abusers is carried out through rehabilitation. There are two types of rehabilitation provided, namely medical rehabilitation and social rehabilitation. The victims of abusers who were caught red-handed by the National Narcotics Agency immediately carried out rehabilitation without due process. While those who were caught red-handed by the Police, even though the evidence was under the provisions of the Circular of the Supreme Court No. 4 of 2010, the legal process continued, after that it was only rehabilitated.